Epitaxial growth of strained and unstrained GeSn alloys up to 25% Sn - Oehme, Michael; Kostecki, Konrad; Schmid, Marc; Oliveira, Filipe; Kasper, Erich; Schulze, Jörg (Thin Solid Films, 2014)
Strained and unstrained GeSn layers on Si substrates were grown with Sn contents up to 20% and 25%, respectively. All metastable layer structures were fabricated by means of an ultra-low temperature molecular beam epitaxy process. The useful thickness of the metastable layers for a range of Sn contents, growth temperatures and two different strain values (unstrained, compressive strained) is explored. The epitaxial breakdown thickness which limits the useful thickness range decreases exponentially with increasing growth temperature and Sn concentration. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2021-06-29
Keywords: GeSn epitaxy; Molecular beam epitaxy; Si photonics; Virtual substrate